Distribution of Ophioglossum reticulatum L. in South America. A case of long-distance jump dispersal? - Meza Torres, Esteban I. (2015)
The objective of this exploratory work is to test the hypothesis that South American populations of Ophioglossum reticulatum L. derive from Africa. Spores cross the Atlantic transported by wind and arrive in South America in recurrent migration. Three-dimensional (backward and forward) trajectories of spores between Africa and South America were calculated using the Hybrid Single Particle Lagrangian Integrated Trajectory Model (HYSPLIT4). The model showed possible backward trajectories in the low troposphere arriving in South America with probable origin in Northwestern Africa. The results support the hypothesis of long-distance dispersal of the studied species. Including vertical motion in the model runs allowed obtaining valuable and novel information about the migration routes. The trade winds combined with the South American monsoon could be a dispersal vehicle for the disseminules from Northwestern Africa to the eastern slopes of the Andes. As the monsoon is a periodic regional atmospheric circulation pattern, transcontinental migration can be assumed to be a recurring phenomenon that provides genetic exchange and prevents speciation by reproductive isolation. Modelled forward trajectories connect the neotropics with Africa-Madagascar, but they seem to be less effective due to their travelling altitudes. This hypothesis might explain the absence of infraspecific taxa restricted to different geographic locations.